Peran Teori Perjanjian Negara Terhadap Terbentuk Negara - Tamaulina Br. Sembiring; Siti Nur Raihani; Yola Fifilyan Salam; Deo Hagatha; Sikapta Ari; Tia Nazla Ramadhani; Dandi Prayoga Nasution; Yuanidar Sitorus; Mesakihiel Suranta Purba Barus (PT PUSTAKA CENDEKIA GROUP, 2024)
This journal discusses how state treaty theory participates in the process of state formation, with special emphasis on how this theory can encourage the establishment of a state. This journal investigates the theories of political philosophers such as Thomas Hobbes, John Locke, and Jean-Jacques Rousseau. It does so by thoroughly analyzing their work. The focus is on how state agreement theory links the formation of real state structures. In addition, this research discusses these theories regarding human rights, government legitimacy, and the development of modern states.